PENGARUH MOTIVASI BELAJAR DAN LINGKUNGAN BELAJAR TERHADAP PRESTASI BELAJAR MATA DIKLAT KOMPETENSI KEJURUAN KELAS XI TEKNIK KENDARAAN RINGAN SEKOLAH MENENGAH KEJURUAN NEGERI 1 KARANGGAYAM KEBUMEN TAHUN AJARAN 2012/2013 - Sugeng Pilihantoro (Jurnal Taman Vokasi, 2013)
The hypothesis in this research are (1) There is a positive influence motivate to learn diklat subject of vocational interest (2) there is and environmental positive influence learn to achievement learn diklat subject of vocational interest and (3) There is a positive influence motivate to vocational interest of class XI technique of light venicle of the country vocational high school 1 karanggayam kebumen of teaching year 2012/2013.The population in this research is all light venicle technique class student of the contry vocational high school 1 karanggayam kebumen of teaching year 2012/2013 a number of 112 students. The sample of research is taken by 95% pursuant to Nomogram Harry King, as much 80 students and 30 students to test drive instrument. This research is inclusive of research of expost facto, while technique of intake of sample use random system (Random Sampling). In analysing data of research used technique of double regresi two prediktor and coleration parsial.From result analyse correlation of parsial obtained (1) The influence which are positive and significant motivate to learn to achievement learn diklat subject of vocational interest, (2) The influence which are positive and significant environment learn to achievement learn diklat subject of vocational interest and (3) The influence which are positive and significant motivate to learn and environmental learn to achievement learn diklat subject of vocational interest of class XI technique of light venicle of the country vocational high school 1 karanggayam kebumen of teaching year 2012/2013.